Islamic Values in Bedhaya Sri Nawa Kumala Dance of Guruh Sukarno Putra Creation - Astarinny , Dinar Ayu; Pramutomo , R.M. (Politeknik Pariwisata NHI Bandung, 2020)
Bedhaya Sri Nawa Kumala dance is a composition of Bedhaya Ketawang Dance idea manifested into a brand new form by Guruh Sukarno Putra, a choreographer and dancer who is experienced in interpreting and reinterpreting. Guruh Sukarno Putra considered that dance can be manifested by exploring the existing value in a community. The value of sacredness as in Bedhaya can be manifested in various forms and shapes. Bedhaya Sri Nawa Kumala dance performance emphasizes Surakarta Traditional Female Dance Style which dance music consisting of the teachings of Sunan Kalijaga contains Islamic values. The costumes cover the head and body of the dancers, which is a manifestation of worship to God Almighty. The method used in this research was dance ethnography with Ethnochoreology approach supported by Marco De Maramis theory explaining that art performance is multilayer. Field research was conducted to obtain data from observation, data analysis, style explanation, and write a synthesis that aims to determine the style of Bedhaya Sri Nawa Kumala dance performance by Guruh Sukarno Putra which contains Islamic Values.